Isolation and Characterization of Cellulase Enzyme from Sago Bettle Larvae - Febryanti, Amalyah; Baharuddin, Maswati; Abeng, Tendri (Chimica et Natura Acta, 2025)
Sago beetle larvae are larvae that consume cellulose and convert it into simple compounds with the help of cellulase enzymes. The enzyme is produced by bacteria found in the larvae's intestines. This study aims to characterize the cellulase enzyme from R8W bacteria, which is a cellulolytic bacterium and derived from sago beetle larvae. The characterization in this research included determination of the optimum temperature, the optimum pH, and the optimum substrate concentration of the enzyme. The methods in this study consisted of the production of enzymes; characterization of cellulase enzyme by DNS method; and measurement of cellulase enzyme activity on natural substrates. The results showed that the cellulase enzyme R8W bacterial isolates from beetle larvae were in optimum conditions respectively at a temperature of 50 °C (enzyme activity of 0.070 U/mL), pH 8 (enzyme activity of 0.069 U/mL), substrate concentration of 2% (enzyme activity of 0.063 U/mL); cellulase enzyme activity of R8W bacterial isolates from sago beetle larvae on rice husk cellulose as a natural substrate was 0.103 U/mL. The characteristics of the cellulase enzyme of R8W bacterial isolate from sago beetle larvae had an optimum temperature of 50 °C, an optimum pH of 8, and an optimum substrate concentration of 2%.